2019
DOI: 10.1155/2019/7957860
|View full text |Cite
|
Sign up to set email alerts
|

The Wound Healing Potential of Aspilia africana (Pers.) C. D. Adams (Asteraceae)

Abstract: Wounds remain one of the major causes of death worldwide. Over the years medicinal plants and natural compounds have played an integral role in wound treatment. Aspilia africana (Pers.) C. D. Adams which is classified among substances with low toxicity has been used for generations in African traditional medicine to treat wounds, including stopping bleeding even from severed arteries. This review examined the potential of the extracts and phytochemicals from A. africana, a common herbaceous flowering plant whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(55 citation statements)
references
References 67 publications
0
54
0
Order By: Relevance
“…ese properties can be attributed to the presence of a wide range of secondary metabolites, including flavonoids, saponins, and tannins (Table 1). Several in vitro and in vivo studies have been carried out on A. africana extracts to determine their anti-inflammatory properties [2,26]. A. africana fresh leaf extract is known for its wound healing potential, which is strongly linked to its anti-inflammatory activity that inhibits the synthesis of prostaglandins and neutrophil migration into the damaged tissues, reduces vascular permeability, and stimulates accumulation of lymphocytes, thus promoting the process of tissue repair [2,19].…”
Section: Anti-inflammatory Properties Of a Africana Extractsmentioning
confidence: 99%
See 1 more Smart Citation
“…ese properties can be attributed to the presence of a wide range of secondary metabolites, including flavonoids, saponins, and tannins (Table 1). Several in vitro and in vivo studies have been carried out on A. africana extracts to determine their anti-inflammatory properties [2,26]. A. africana fresh leaf extract is known for its wound healing potential, which is strongly linked to its anti-inflammatory activity that inhibits the synthesis of prostaglandins and neutrophil migration into the damaged tissues, reduces vascular permeability, and stimulates accumulation of lymphocytes, thus promoting the process of tissue repair [2,19].…”
Section: Anti-inflammatory Properties Of a Africana Extractsmentioning
confidence: 99%
“…Inflammation is a natural biological and complex reaction, typically of mammals, to a wide range of belligerent agents such as pathogens, parasites, harmful chemicals, and physical tissue injury [1]. Inflammatory response is a protective effort by the bodies of organisms to eliminate harmful stimuli and initiate the healing process in damaged tissues [2]. During inflammation, the body institutes a biochemical cascade that prompts responses geared toward healing the damaged tissue.…”
Section: Introductionmentioning
confidence: 99%
“…It improves Sodo University Teaching and Referral Hospital, Southern Ethiopia healing and prevents complications of existing pressure ulcer. This is because nurses have a responsibility to monitor patient's skin in order to plan, implement and evaluate interventions that maintain skin integrity by using their knowledge and skill [3,[13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Despite advances in medical technology and the use of formal prevention programs based on clinical practice guidelines, the prevalence of bed sore during hospitalization continues to increase to 80%. The study finding on prevalence and associated factors of pressure ulcer among hospitalized patients in Felege Hiwot referral hospital revealed that 16.8% of them had pressure ulcer in Ethiopia [2,13,15].…”
Section: Introductionmentioning
confidence: 99%
“…C.D. Adams rich in BCP showed wound healing ability by reducing wound bleeding, enhancing wound contraction, increasing concentration of basic fibroblast growth factor and platelet-derived growth factor along with increasing white and red blood cells [ 130 ]. These studies intend that BCP has the potential to be developed for dermatological use specially in wound healing.…”
Section: β-Caryophyllene In Diabetic Complicationsmentioning
confidence: 99%